Influence of microstructural changes on the macro response of functionally graded material structures. (November 2015) - Cheng, M. H.; Cao, Y. Z.; Peng, H. W.; Yang, G. Y.
Abstract : Macro structural properties of functionally graded material depend on micro net structures. Thus, there is important theoretical significance in studying the influence of material microstructural changes on the macro responses of functionally graded material structures. Here, a new microelement method is proposed. Scale-span analyses between macro responses and micro-constitution were conducted based on metallography input instead of traditional mechanical input of materials parameters. To reflect the actual microstructural changes in functionally graded materials, the microelement method established dense microelements in the normal finite element of the structure, and translated the freedom degrees of all microelemental nodes to the freedom degrees of the same normal finite elements by compatibility conditions. Three-dimensional mechanical analyses of functionally graded material plates with medium components and micro net structures were determined by the microelement method, and the influence of the microstructural changes on macro response distributions was analysed.